SYNERGY OF MSMES AND BLUE ECONOMY FOR SUSTAINABLE DEVELOPMENT IN THE COASTAL AREAS OF EAST KALIMANTAN - Jainuddin, Jainuddin; Anggraini, Leny Susilawati; Halik, Abdul; Mujanah, Siti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to identify and analyze the synergy between MSMEs and the blue economy in supporting sustainable development in the coastal areas of East Kalimantan. The research was conducted in several regencies in East Kalimantan, namely Balikpapan, Paser, Bontang, Kutai Kartanegara, and Kutai Timur. These regions were selected due to their significant maritime-based economic activities. Data collection was carried out for two months. This research employs a qualitative approach to explore the perceptions, experiences, and views of MSMEs related to the blue economy. The research results indicate that the synergy between MSMEs and the blue economy concept not only has a positive impact on improving the welfare of coastal communities but also serves as a strategic step in preserving marine ecosystems. Through strengthened collaboration among stakeholders, MSMEs can become the driving force behind an inclusive and sustainable blue economy.